2020
DOI: 10.1177/1354816620932808
|View full text |Cite
|
Sign up to set email alerts
|

Festival value in multicultural contexts: City festivals in South Africa

Abstract: Worldwide, the number and variety of cultural festivals have grown dramatically. Many areas see festivals as an important way to attract tourists, and their spending, to a region, resulting in a positive economic impact. While they offer important opportunities for artistic producers and audiences, there is growing pressure for festival organizers to demonstrate their value to society beyond their economic impact. Like many countries, South Africa has a strong focus on increasing diverse cultural part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 30 publications
(38 reference statements)
0
6
0
Order By: Relevance
“…This bibliography is very oriented to the study of cultural tourism; a high proportion analyzes the tourist dynamics in historic centers and how they contribute to the construction of destinations and to urban regeneration. Less frequent but of great interest are publications oriented to analysis of tourism segmentation and the creation of specialized cultural products, such as museums (Gómez, 2012) or cultural festivals (Barrera-Fernández et al, 2017;Georgoula & Terkenli, 2018;Gómez & Guzmán, 2017;Snowball & Antrobus, 2020), along with works related to language tourism (Pardo-Abad, 2011). Also noteworthy are studies like those by Vázquez-Varela and Martínez-Navarro (2016) that analyze the impact that high-speed rail development has had on tourism in medium and small cities, or those that delve into aspects related to sustainability (Del Espino Hidalgo et al, 2016).…”
Section: Theoretical Framework and State Of The Questionmentioning
confidence: 99%
“…This bibliography is very oriented to the study of cultural tourism; a high proportion analyzes the tourist dynamics in historic centers and how they contribute to the construction of destinations and to urban regeneration. Less frequent but of great interest are publications oriented to analysis of tourism segmentation and the creation of specialized cultural products, such as museums (Gómez, 2012) or cultural festivals (Barrera-Fernández et al, 2017;Georgoula & Terkenli, 2018;Gómez & Guzmán, 2017;Snowball & Antrobus, 2020), along with works related to language tourism (Pardo-Abad, 2011). Also noteworthy are studies like those by Vázquez-Varela and Martínez-Navarro (2016) that analyze the impact that high-speed rail development has had on tourism in medium and small cities, or those that delve into aspects related to sustainability (Del Espino Hidalgo et al, 2016).…”
Section: Theoretical Framework and State Of The Questionmentioning
confidence: 99%
“…Festivals in South Africa before COVID-19 were a booming sector: In 2018, Van Heerden and Saayman (2018) found that there were more than 600 festivals of various kinds per year in South Africa. Although some of them were already starting to experience a drop in visitor numbers (and spending) as South African economic growth slowed, festivals were still seen as an excellent way to increase tourist spending, support the creative economy, and improve access to arts and culture for audiences (Snowball and Antrobus, 2021).…”
Section: Context: Creative Industries In South Africa and The South A...mentioning
confidence: 99%
“…The Rhodes University research team are also linked to the creative industries through the South Africa Cultural Observatory (SACO), which is a national research organisation funded by the Department of Sport, Arts and Culture. Involvement with SACO meant that the research team were in a good position to engage with the sector, building on previous work on the impact and development of festivals, and other parts of the creative economy, in South Africa (SACO, 2022; Snowball and Antrobus, 2021; Snowball and Gouws, 2022)…”
Section: Introductionmentioning
confidence: 99%
“…It is due to the change of policy and travel mode, resulting in a high concentration of people traveling during the holidays, causing huge traffic pressure on the traffic network and tourism activities in some tourist cities, and indirectly reducing the pleasure of tourists' travel [9][10][11]. Therefore, the problem of holiday tourism traffic congestion and the problem of activity effects have gradually become an unfavorable factor that restricts the development of tourism-based city transportation and tourism economy [12][13].…”
Section: Introductionmentioning
confidence: 99%